TYPES AND ABUNDANCE OF PHYTOPLANKTON AT DIFFERENT DEPTHS IN THE COASTAL WATERS OF TELUK MAKMUR VILLAGE, DUMAI CITY, RIAU - Shandy, Jacinda Qoidatun; Nasution, Syafruddin; Nurrachmi, Irvina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This study aims to identify the types and abundance of phytoplankton at different depths and research stations in the coastal waters of Teluk Makmur Village, Dumai City, Riau Province. Samples were taken from three different locations, namely estuary areas, tourist areas, and areas far from settlements. The number of phytoplankton samples from the three stations at three depths was 27 samples. Water quality parameters such as temperature, salinity, pH, DO, TSS, nitrate and phosphate were measured to determine the condition of the aquatic environment and the effect on phytoplankton growth. Phytoplankton were analyzed using a microscope and identified using a phytoplankton identification book. The results showed that 27 species of marine phytoplankton were found in the Bacillariophyceae, Dinophyceae, Cryptophyceae, and Conjugatophyceae classes. The most common phytoplankton found came from the Bacillariophyceae class. The highest abundance of phytoplankton between depths was obtained from a depth of 3 m, namely 368,558.0441 ind/L, while the highest abundance of phytoplankton between stations was obtained from station III, namely 360,000.452 ind/L. The abundance of phytoplankton between depths and between stations showed no significant difference (p>0.05).